Intercultural Influences of Neighboring Communities on Olùkùmí Speakers: A Case Study of Ugbódu (Integral Research, 2025)
Neighbouring communities can influence a particular community's speech form, and cultural belief, especially if the community is smaller than others. Such is the case of Ugbódù, an Olùkùmi speaking community that is sandwiched among Igbo speakers in Delta state, and shares a boundary with Esan speakers of Edo state, Nigeria. This paper aims to investigate the influence of Igbo and Esan/Edo languages on Olùkùmi and its extent. This will contribute to the knowledge that a dominant community usually has a magnitude effect on the enclave one i.e. the minority group. Data for this paper are drawn from our research visit to Ugbódù. Competent native speakers and custodians of the heritage of the community were interviewed such as the Ọlọ́zà of Ugbódù. Based on the Acculturation Model Theory, this paper shows that language contact has made acculturation inevitable and has a psychological and sociocultural influence on the enclave Ugbódù. Amongst the findings, it is observed that Olùkùmi speakers are predominantly Olùkùmi-Ìgbò bilinguals. Furthermore, the influence of Edo and Igbo is well-pronounced in the social and cultural life of Ugbódù people. In protecting and preserving Olùkùmi, Ugbódù people are taking radical revival steps to instil the love of Olùkùmi in its speakers to guard against its future loss. In conclusion, this paper shows that if a drastic measure is not taken, a dominant language(s) can threaten a dominated group and even result in assimilation acculturation.
Keywords: Acculturation Theory, Cultural Diversity, Intercultural Influence, Olùkùmi, Speech Community.